Генетическое разнообразие вируса лейкоза крупного рогатого скота и его распространение в районах Республики Дагестан - D. A. Baboshko; M. G. Daudova; P. Y. Achigecheva; K. A. Elfimov; D. K. Dandamaev; Z. R. Shakhbanova; A. V. Totmenin; N. M. Gashnikova (Юг России: экология, развитие)
To study the spread of infection caused by the bovine leukemia virus in farms of the Republic of Dagestan.PCR diagnostics of 212 cattle blood samples collected in farms of the Kizlyarsky, Kumtorkalinsky and Tabasaransky districts was performed for the presence of bovine leukemia virus DNA (BLV). For BLV-positive samples, nucleotide sequences of the viral genome fragment encoding the main envelope protein (env) were deciphered, and the virus genotype was determined. Phylogenetic relationships of the isolated BLV varians with previously described bovine leukemia viruses were studied.The representation of virus genotypes among 80 BLV isolated in the studied districts differed significantly. In the Kizlyarsky and Kumtorkalinsky districts, G7 leukemia viruses were found in 7.4 %, and the G4 genotype was isolated in 92.6 %. In one farm in the Tabasaran district, 2 G7 variants and one G4 variant were found. At the same time, 10 out of 11 G7 variants were grouped with each other into three statistically significant clusters, including the studied BLV, which indicates virus transmission within and between farms. Phylogenetic analysis of 69 BLV of the G4 genotype allowed us to conclude that a heterogeneous G4 population circulates in Dagestan. Analysis of cases of leukemia infection of young animals in unfavourable farms and the presence of phylogenetic clusters of close BLV confirm that at present the main reason for registering new BLV cases is not the introduction of BLV during the purchase of breeding cattle, but the transmission of infection within the territories of the Republic.Molecular genetic analysis of BLV isolated in Dagestan allowed us to describe the related chains of virus spread both within one farm and between farms. The results of phylogenetic studies of BLV have great practical significance and can be used in planning effective anti-epizootic measures in Dagestan. In addition to great practical significance, the work performed demonstrates novelty, as it makes a significant contribution to the study of molecular epidemiology of BLV in Russia.